Effect of Extract Cocor Bebek (Bryopyllum pinnatum) to the Amount of Th17 Cells Spleen and Levels of IL-17A Serum in Mice Balb/C Pregnant Model of Systemic Lupus Erithematosus - Umi Kalsum (Journal of Global Pharma Technology, 2019)
This study aims to determine a way to reduce the number of Th17 cells spleen and serum levels of IL 1A heart in mice Balb /C pregnant models with Systemic Lupus Erythematosus. This was studied, using mice Balb / C pregnant models with SLE. This study is divided into 5 groups: negative control, positive control, and treatment provision Bryophyllum Pinnatum dose of 10.5 mg/day, 21 mg/day and 42 mg/day. The Th cell number 17 was measured through flow cytometry. Levels of IL 17A were measured using the ELISA method. The data was analyzed using the Kruskal Wallis test. Giving bryophyllum Pinnatum dose 21mg / day (2.79 ± 1.484) has been proven to reduce the number of Th17 cells in mice Balb / C pregnant models with SLE when compared to the other dose treatment. Although, it did not significantly affect (p> 0.05).There was no difference with the increased levels of IL bryophyllum Pinnatum 17A in Balb / C mice pregnant models with SLE (p> 0.05). Conclusion: Giving bryophyllum Pinnatum has been proven to reduce the number of Th 17 cells in mice pregnant models with SLE.Keywords: Systemic Lupus Erythematosus (SLE), Bryopillum Pinnatum, Th17, IL 17A.